The dynamics of social practice everyday life and how it changes - Shove, Elizabeth 1959-; Pantzar, Mika; Watson, Matt (Sage Publications, 2012)
Everyday life is defined and characterized by the rise, transformation and fall of social practices. Using terminology that is both accessible and sophisticated, this book guides the reader through a multi-level analysis of this dynamic. The book provides discussion of real world examples such as the history of car driving and the emergence of frozen food, bringing abstract concepts to life and grounding them in empirical case-studies and new research. Demonstrating the relevance of social theory for public policy problems, the authors show that the everyday is the basis of social transformation.